CAV-2-Mediated GFP and LRRK2G2019S Expression in the Macaca fascicularis Brain - di Caudo, Carla; Martínez-Valbuena, Ivan; Mundiñano, Iñaki-Carril; Gennetier, Aurelie; Hernandez, Maria; Carmona-Abellan, Mar; Marcilla Garcia, Irene; Kremer, Eric J.; Luquin, Rosario (Frontiers in Molecular Neuroscience, 2020)
Parkinson’s disease is characterized by motor and nonmotor symptoms that gradually appear as a consequence of the selective loss of dopaminergic neurons in the substantia nigra pars compacta. Currently, no treatment can slow Parkinson’s disease progression. Inasmuch, there is a need to develop animal models that can be used to understand the pathophysiological mechanisms underlying dopaminergic neuron death. The initial goal of this study was to determine if canine adenovirus type 2 (CAV-2) vectors are effective gene transfer tools in the monkey brain. A second objective was to explore the possibility of developing a large nonhuman primate that expresses one of the most common genetic mutations causing Parkinson’s disease. Our studies demonstrate the neuronal tropism, retrograde transport, biodistribution, and efficacy of CAV-2 vectors expressing GFP and leucine-rich repeat kinase 2 (LRRK2G2019S) in the Macaca fascicularis brain. Our data also suggest that following optimization CAV-2-mediated LRRK2G2019S expression could help us model the neurodegenerative processes of this genetic subtype of Parkinson’s disease in monkeys.